2016
DOI: 10.1108/jqme-12-2015-0064
|View full text |Cite
|
Sign up to set email alerts
|

Human factors in maintenance: a review

Abstract: Purpose – The purpose of this paper is to review current literature analyzing human factors in maintenance, and areas in need of further research are suggested. Design/methodology/approach – The review applies a novel framework for systematically categorizing human factors in maintenance into three major categories: human error/reliability calculation, workplace design/macro-ergonomics and human resource management. The framework further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 65 publications
(56 reference statements)
1
36
0
Order By: Relevance
“…Therefore, it can be argued that by improving the level of knowledge and experience, the company could improve the effectiveness of maintenance strategy. Human factors are therefore important aspects to be considered in the field of maintenance [44].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it can be argued that by improving the level of knowledge and experience, the company could improve the effectiveness of maintenance strategy. Human factors are therefore important aspects to be considered in the field of maintenance [44].…”
Section: Discussionmentioning
confidence: 99%
“…Occupational ergonomics focuses primarily on work-related health and safety aspects of a system to reduce the rate of employee health problems. However, in recent years there has been a growing interest in what we call system performance ergonomics, both in the operation [56] and maintenance [57] of industrial systems. Sobhani et al [56] provide a road map for assessing the impact of work-related risk factors, including physical and psychosocial aspects on system performance.…”
Section: B Ergonomic Contextmentioning
confidence: 99%
“…However, its focus was on assessing the cost growth of a manufacturing system due to the low ergonomic design of the workplace rather than human failure issues. Sheikhalishahi et al [57] reviewed the current literature analyzing human factors in maintenance considering three main categories: (1) error calculation / human reliability, (2) human resource management and (3) workplace design / macro ergonomics. They found that even though most studies focus on macroergonomics, human factors in maintenance are a pressing problem, as reported in the few articles that dealt with ergonomic factors-induced human errors in maintenance.…”
Section: B Ergonomic Contextmentioning
confidence: 99%
“…While safety is related to proper maintenance of equipment (Lind et al. ), there is little research on how safety climate impacts unplanned maintenance in commercial vessels (Sheikhalishahi ). In the logistics literature, only a few studies have examined the impact of safety climate.…”
Section: Hypothesis Developmentmentioning
confidence: 99%